1995
DOI: 10.1103/physrevb.52.r8643
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of buried Si layers in GaAs(001) as studied by soft-x-ray emission

Abstract: It is demonstrated that it is possible to investigate details of the electronic structure of an internal atomic monolayer using soft-x-ray-emission spectroscopy. The local and partial density of states of one monolayer and three monolayers of Si, embedded deep below a GaAs(001) surface, was extracted. Clear differences to the density of states for bulk Si were observed.Original Publication:P. O. Nilsson, J. Kanski, J. V. Thordson, T. G. Andersson, J. Nordgren, J. Guo and Martin Magnuson, Electronic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…This effect is significantly larger and completely opposite from that in Si L 2,3 spectra of pure single crystal Si(111). 9,31 The enhanced Si 3d (electron-like) intensity along the c axis of Ti 3 SiC 2 should reduce and compensate for the dominating hole-like Ti 3d bands that give negative contributions to the Seebeck coefficient along the c axis. In particular, it should be noted that this strong intensity of the Si 3d character weighting in the partial DOS observed experimentally along the c axis at room temperature is not at all reproduced in ground state DFT theory at zero Kelvin but is instead opposite in the energy range 1-3 eV below E F .…”
Section: B C K X-ray Absorption and Emissionmentioning
confidence: 99%
“…This effect is significantly larger and completely opposite from that in Si L 2,3 spectra of pure single crystal Si(111). 9,31 The enhanced Si 3d (electron-like) intensity along the c axis of Ti 3 SiC 2 should reduce and compensate for the dominating hole-like Ti 3d bands that give negative contributions to the Seebeck coefficient along the c axis. In particular, it should be noted that this strong intensity of the Si 3d character weighting in the partial DOS observed experimentally along the c axis at room temperature is not at all reproduced in ground state DFT theory at zero Kelvin but is instead opposite in the energy range 1-3 eV below E F .…”
Section: B C K X-ray Absorption and Emissionmentioning
confidence: 99%
“…In a study of Si(100) buried in GaAs, it has been demonstrated that it is in fact possible to extract detailed information about DOS [83]. By irradiating the sample with a bright source, it is possible to detect characteristic fluorescence from buried layers.…”
Section: Buried Atomical Layers and Interfacesmentioning
confidence: 99%
“…As in the case of Al, the Si L 2,3 spectrum is dominated by 3s final states and the Si 3p states are dipole forbidden. The spectral profile of Si in Ti 3 SiC 2 also largely differs from spectra of pure Si, which has a pronounced double structure [13]. The spectral shape of Si in Ti 3 SiC 2 is similar to the metal silicides [14].…”
Section: Resultsmentioning
confidence: 80%
“…The measured spectral profiles of Al, Si and Ge are compared to spectra of the pure elements from Refs. [11,13,15] (dashed lines). The Ge spectrum (bottom) was smoothed with a binomial average of the raw data.…”
Section: Resultsmentioning
confidence: 99%